2022
DOI: 10.3390/clinpract12050087
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Artery Pseudoaneurysm after an Uncomplicated Vaginal Delivery: A Case Report

Abstract: Uterine artery pseudoaneurysm (UAP) is a rare and potentially life-threatening vascular anomaly caused by inadequate sealing of a ruptured wall of a uterine artery. It mainly occurs after a traumatic lesion and can lead to delayed postpartum hemorrhage. We report a rare case of UAP after an uncomplicated vaginal delivery in a patient with a history of deep-infiltrating endometriosis. Selective coil embolization was successfully performed. UAPs should always be considered in cases of unexplained abdominal pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It can lead to delayed postpartum hemorrhage. Böckenhoff et al [ 27 ] reported a rare case of this condition after an uncomplicated vaginal delivery in a patient with a history of deep-infiltrating endometriosis. Selective coil embolization was successfully performed.…”
mentioning
confidence: 99%
“…It can lead to delayed postpartum hemorrhage. Böckenhoff et al [ 27 ] reported a rare case of this condition after an uncomplicated vaginal delivery in a patient with a history of deep-infiltrating endometriosis. Selective coil embolization was successfully performed.…”
mentioning
confidence: 99%